Ultrafast Broadband Nonlinear Optical Response in Co-Doped Sb2Se3 Nanofilms at Near-Infrared - Sun, Di; Fang, Yu; Yan, Xiaoyan; Shan, Wen; Sun, Wenjun; Meng, Qingyu (Frontiers in Materials, 2021)
Transition metal-doped Sb2Se3 has become a heated topic caused by the strong nonlinear optical response and the ultrafast response time at high laser excitation. In this paper, the Co-doped Sb2Se3 with different doping amount (0.5, 1.0, and 1.5 W) nanofilms were prepared by magnetron sputtering technology, and the nonlinear behavior of Co-doped Sb2Se3 nanofilms at near infrared were systematically studied. The results of the femtosecond Z-Scan experiment indicate that the Co-doped Sb2Se3 nanofilms exhibit broadband nonlinear response properties owing to the free carrier absorption, the Kerr refraction, the two-photon absorption, and the free carrier refraction. The nonlinear absorption coefficients of Co-doped Sb2Se3 nanofilms are from 3.0 × 10−9 to 2.03 × 10−8 m/ W under excitation at 800, 980, and 1,030 nm, and the nonlinear refractive index of the Co-doped Sb2Se3 nanofilms is from 4.0 × 10−16 to -3.89 × 10−15 m2/ W at 800, 980, and 1,030 nm. More importantly, Co-doped Sb2Se3 (1.5 W) nanofilm exhibits ultrafast carrier absorption (<1 ps) and a stronger transient absorption intensity of ΔOD > 6.3. The Co-doping content can controllably tune the crystalline degree, the ultrafast carrier absorption, the intensity of the reverse saturation absorption, the broadband nonlinear optical response, and the carrier relaxation time of Co-doped Sb2Se3 nanofilms. These results are sufficient to support their applications in broadband nonlinear photonic devices.